Development of air ﬂow control device for industrial and social buildings of JSC Russian Railways - S. N. Naumenko; P. O. Muserskiy (Вестник Научно-исследовательского института железнодорожного транспорта, 2025)
Introduction. The authors considered ways of reducing costs of building maintenance as a solution of one of the target tasks of the JSC Russian Railways. The air ﬂow standards may be achieved with lower heat and electricity consumption through the use of energy efﬁcient ventilation systems. Automated systems for controlling the ﬂow of air supply and exhaust ventilation were observed. Analysis of the principle of operation of these systems allowed to develop a prototype of an innovative device and test it on various facilities of JSC Russian Railways, thereby achieving reduction of energy consumption.Materials and methods. Methods of ﬁeld tests of ventilation system on a stand for ﬁlters to purify air entering passenger car space and ﬁeld comparative tests at sanatorium of JSC Russian Railways were applied.Results. The feasibility of using air ﬂow control devices of ventilation systems, comparative tests of which performed on production and social facilities of JSC Russian Railways, were scientiﬁcally proven, demonstrated reliable operation and stable savings in energy consumption, compared to the standard operating modes of ventilation.Discussion and conclusion. The results of the work enable to afﬁrm that application of the developed prototype of the air ﬂow control device in ventilation systems of production and social buildings of JSC Russian Railways would ensure reduction of energy consumption while maintaining normalised parameters of the air volumes passing through the air ducts.